A Qualitative and quantitative assessment of a leadership training programme’s impact on health system performance in 19 counties in Kenya - Chelagat, Tecla (Strathmore University, 2020)
Health service delivery was devolved from the national Government to the counties in 2013 following the adoption of a new constitution in 2010. The aim was to make service delivery more efficient through closer leadership oversight at the counties. However, evidence suggests that health system performance in Kenya remains poor as manifested by inadequate funding and inefficient use of available resources. The main issue appears to be inadequate leadership at national and county levels. To address this issue, several institutions in Kenya have implemented training programmes targeting healthcare leaders. However, most of such training in Kenya focus on “leaders” (individual) development as opposed to “leadership” training (development of groups from an organization). The former approach has been shown to be ineffective in transforming institutional health system performance. The goal of the study was to examine the effect of a project-based leadership training implemented at Strathmore University since 2013 on health system performance in selected Counties in Kenya. A multi-method research design comprising of quasi-experimental time-series and qualitative methods was employed. Questionnaires and in-depth interviews were administered to 39 health managers from the public, private and faith-based institutions from 19 counties in Kenya who had undergone the leadership training followed by coaching and implementation of an institutional improvement project. The control group comprised 39 other health institutions within the same counties with managers that did not receive the leadership training. The proxy measure of the success of the leadership training was completion of implementation of the institutional improvement project. Thirty-three (85%) of the projects were successfully implemented and 29 (88%) and were sustained for a period of 60 months after the leadership training. Control health institutions had no health system performance enhancement activities during the same period. A responsive (health system performance enhancement) leadership training curriculum, alignment of the project to the County’s strategic plan and stakeholders buy-in and support for the programme were reported as the key project implementation and sustainability enablers. These findings show that leadership training and team coaching built around priority institutional improvement projects result in measurable and sustainable health system performance improvements indicators.
Submitted in total fulfillment of the requirements for the Degree of Doctor of Philosophy in Health System Management at Strathmore University
Keywords: Impact; Sustainability; Health systems performance; Leadership development; Team coaching.